(untitled) (Herald of Journalism, 2018)
This article deals with the highlights important trends in the global media system development, along with the accelerated development of modern information technologies. Indeed, this process has an impact on the development of today’s Kazakh journalism. As a result, there have been some changes in the content of the material, genre, and media imaginative features. All newspapers and magazines have created their own websites and internet versions. Radio and television channels also find effective ways to distribute programs on the Internet. All this has reduced the dependence on the information space and time, has expanded its opportunities for efficiency and exchange. As a result, the volume of information capacity significantly increased the media interactive content. They, through feedback from the recipients of information and the opportunity to communicate, opened the way for the development of citizen journalism. Civil journalism is formed in our country. Its first symbols can be seen at the stage of dynamic development of the Kazakh blogosphere of seven or eight years ago. ISSN 1563-0242 Herald of journalism. №2 (48). 2018 71 Білдебековa Ә.Т. Media raised current issues of our life, express ideas and suggestions of the people, represent different views and opinions. It is a true tribune of pluralism, so the media should create new opportunities for their customers.At the moment, the media formed a close relationship with audience, drawing ordinary people to the media work and collecting information. What does it mean? The conversion of anxiety and social problems of everyday life in the main theme of the day indicates the occurrence of the phenomenon of citizen journalism. Citizen journalism helps to the active process indissemination of information through the media. Key words: Information, media, civil journalism, mass media, article.